(untitled) (World Science, 2016)
National standards harmonized with international, which are fundamental for the creation of efficient energy management systems. However, the requirements of Directive 2012/27 / EU fully expedient is to harmonize all the ISO 50000 series of standards, as well as the related series of standards EN 16247 (energy audits), ISO 11011 (evaluation of the energy efficiency of compressed air systems), ISO / ASME 14414 (evaluation energy pump installations), ISO 80000-1 and IEC 60027 series (scientific and mathematical quantities and their units, letter symbols), ISO / IEC / TS 17022 (requirements and recommendations for the content of the report of the Audit management system, conducted by a third party), ISO / IEC / TS 17023 (installation for determining the duration of the certification audits of management systems), ISO / TR 16344 (terms, definitions and symbols to assess the energy performance and energy certification of buildings), ISO 16818 (the terminology of energy efficiency in the design of engineering systems of buildings) , ISO 17747 (determination of the energy saving potential in organizations), ISO / IEC guide 98-3 (guide to the expression of uncertainty in measurement).